Investigating the anticancer efficacy of biogenic synthesized MgONPs: An in vitro analysis - Tabrez, Shams; Khan, Azhar U.; Hoque, Mehboob; Suhail, Mohd; Khan, Mohammad Imran; Zughaibi, Torki A. (Frontiers in Chemistry, 2022)
The biogenic approach of synthesizing metal nanoparticles is an exciting and interesting research area with a wide range of applications. The present study reports a simple, convenient, low-cost method for synthesizing MgONPs from pumpkin seed extract and their anticancer efficacy against ovarian teratocarcinoma cell line (PA-1). The characteristic features of biogenic MgONPs were assessed by UV-visible spectrophotometry (UV-vis), X-ray powder diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The formation of spherical NPs with an average size of 100 nm was observed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Moreover, MgONPs exhibit considerable cytotoxicity with IC50 dose of 12.5 µg/ml. A dose-dependent rise in the induction of apoptosis, ROS formation, and inhibition in the migration of PA-1 cells was observed up to 15 µg/ml concentration, reflecting its significant anticancer potential against ovarian teratocarcinoma cell line. However, additional work, especially in different in-vitro and in-vivo models, is recommended to find out its real potential before this environment-friendly and cost-effective nanoformulation can be exploited for the benefit of humankind.